(untitled) (مجلة المنصور, 2023)
Modern buildings have a lot of ducts and pipelines because they need to have services like air conditioning, electricity, and the phone. These services can be put in place through openings in the webs of concrete beams. One of the problems faced by buildings is exposure to high temperatures. Therefore, adequate structural fire resistance should be provided to resist this situation, or at least allow residents time to escape before stability fails. Very little research has been done regarding reinforced concrete RC beams containing web openings under the impact of high temperatures. The present paper aims to compile this state of work on the performance of RC beams with openings under high temperatures. There are many different topics that will be covered and emphasized like the classification of openings, the behavior of reinforced concrete beams with openings, steel bars and concrete mechanical properties at high temperature, and the performance of reinforced concrete beams subjected to high temperature. Finally, suggestions are made for future studies based on the gaps shown in the existing body of work.